Analysis Of Student Discipline Characters Of Grade V At SDN Tambakbaya - Nurmala, Mita; Suryana, Dudung; Nugraha, Fajar (Universitas Dehasen Bengkulu, 2025)
This research aims to analyze the implementation of positive discipline through routine habituation programs for fifth-grade students at SDN Tambakbaya and to identify the obstacles encountered during the process. This study employs a qualitative approach with a descriptive method. The research subjects include the fifth-grade teacher, the principal, and ten students with high and low attendance levels. Data collection techniques include observation, interviews, and documentation. The findings show that positive discipline is implemented through various habituation programs such as dhuha prayer, morning literacy, healthy exercise, and the 5S culture (smile, greet, salute, polite, courteous). These programs foster student discipline as reflected in punctuality, adherence to school rules, and responsibility for tasks. However, challenges include student inconsistency, diverse individual characters, and teachers’ limited time for supervision. It is concluded that positive discipline is effective in shaping students’ character but requires consistent support from the entire school community.